Elucidation of the Electrocatalytic Function of Composite Metal Carbides Co3W3C and Co3Mo3C with Oxygen Reduction and Oxygen Evolution Reactions - Ikki YANAGIMOTO; Masashi WADA; Satoko TAKASE; Toshiyuki TAKIZAWA; Youichi SHIMIZU (Electrochemistry)
Metal-air secondary batteries have attracted attention as a next-generation energy storage system due to their high energy density and environmentally friendly characteristics. However, it is important to develop a catalyst that can rapidly promote both the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER). We have found that Co3W3C and Co3Mo3C composite metal carbides prepared by a wet method have high bifunctional electrode performance, but the mechanism of action has not been elucidated. In this study, we comprehensively evaluated the adsorption behavior of oxygen molecules and surface hydroxyl groups, the charge density difference, and the effects of surface structure and chemical composition on catalytic activity by combining DFT (density functional theory) calculations and instrumental analysis. In particular, we found that Co3Mo3C optimizes the adsorption of oxygen molecules by metal compositing, contributing to the improvement of electrode catalytic performance.